The additive effect of iloprost on the biological properties of Mineral trioxide aggregate on mesenchymal stem cells - Alanoud Almeshari; Mona Elsafadi; Randa Almadhari; Amer Mahmood; Sara Alsubait; Hacer Aksel (Elsevier, 2022)
Background/purpose: Iloprost has been proposed as a potential biomaterial owing to angiogenic and odontogenic properties. However, the liquid form can limit its use during clinical applications. Mineral trioxide aggregate (MTA) has been used for various dental applications in which cell-material interaction is essential. This study aimed to investigate additive effects of iloprost on the biological properties of MTA on the viability, attachment, migration and differentiation of human mesenchymal stem cells (hMSCs). Materials and methods: Standardized human dentin disks were prepared. MTA was prepared by mixing distilled water or iloprost solution, and the lumen of the disks was filled with MTA or MTA-iloprost. hMSCs on disk alone and hMSCs on culture plates were used as controls. Cell viability and attachment were measured after 1, 7 and 14 days using AlamarBlue assay and scanning electron microscopy (SEM). Cell migration in MTA or MTA-iloprost extracts was determined using a wound-healing model.Osteogenic differentiation was evaluated by real-time reverse transcriptase polymerase chain reaction for alkaline phosphatase (ALP), bone sialoprotein (BSP), osteocalcin (OCN), and osteopontin (OSP) gene expressions after 7 and 14 days of osteogenic induction. Results: Cells on MTA-iloprost surface showed similar viability with MTA at 1 and 14 days but enhanced cellular viability and cell spreading compared to MTA at 7 days (p < 0.05). Cell migration was similar by MTA-iloprost and MTA extracts (p > 0.05). MTAiloprost significantly upregulated BSP, OCN and OSP expressions compared to MTA (p < 0.05). Conclusion: The addition of iloprost to MTA improved the initial cell viability and osteogenic potential of hMSCs.